Complete response of metastatic melanoma in a patient with Crohn's disease simultaneously receiving anti-α4β7 and anti-PD1 antibodies. Issue 1 (6th January 2019) - Frohne, Christopher C.; Llano, Ernesto M.; Perkovic, Ashley; Cohen, Russell D.; Luke, Jason J.
Abstract : Background: Immune checkpoint inhibitors (ICPIs) are increasingly being used in the treatment of a variety of malignancies. The original studies that demonstrated the efficacy of ICPIs excluded patients actively being treated for autoimmune conditions, and there is only limited evidence that these treatments are safe and effective in this population of patients. Case presentation: We present a case of a man with Crohn's disease actively requiring immunosuppressive therapy who subsequently received pembrolizumab for metastatic melanoma. He had no further progression of metastatic disease and had resolution of his pulmonary nodule while he experienced no Crohn's disease flares or immune related adverse events. We surveyed the existing literature for studies examining the use of ICPIs in patients with autoimmune disorders and reviewed the unique mechanism of action of the α4β7 inhibitor, vedolizumab. Conclusion: Patients with autoimmune conditions should be considered candidates for immune checkpoint inhibition even in the setting of active immunosuppressive therapy. The mechanism of action of immunosuppressive therapy should be considered with the most targeted form of treatment being used when possible. Further prospective studies investigating immunotherapy in patients with autoimmune conditions are warranted.